2014
DOI: 10.1136/annrheumdis-2014-eular.2855
|View full text |Cite
|
Sign up to set email alerts
|

THU0409 Leucine-Rich Alpha2-Glycoprotein is A Useful Biomarker for Monitoring of Disease Activity in Patients with Adult-Onset Still's Disease

Abstract: Background Leucine-rich alpha2-glycoprotein (LRG) is a protein which contains leucine-rich repeats. Though physiologic functions of LRG have not been clearly defined, its expression was up-regulated during neutrophil differentiation and its levels were significantly elevated in some chronic inflammatory diseases such as inflammatory bowel disease. Objectives Our study aimed to investigate whether serum leucine-rich α2-glycoprotein (LRG) levels are elevated in patients with adult-onset Still's disease (AOSD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In active LN, the inflammatory and autoimmune reactions were more serious. In previous study, serum LRG1 concentrations correlated with disease activity in SLE, rheumatoid arthritis, Crohn's disease, ulcerative colitis and adult-onset Still's disease [12,20,22,24,32].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In active LN, the inflammatory and autoimmune reactions were more serious. In previous study, serum LRG1 concentrations correlated with disease activity in SLE, rheumatoid arthritis, Crohn's disease, ulcerative colitis and adult-onset Still's disease [12,20,22,24,32].…”
Section: Discussionmentioning
confidence: 80%
“…The precise function of LRG1 remains unknown, but accumulating evidences showed that LRG1 is closely correlated with various types of cancers, such as lung, oral, ovarian, gastrict, pancreatic and biliary tract cancers [14][15][16][17][18]. Moreover, LRG1 is identified as an inflammatory protein in human serum and highly expressed in various kinds of benign inflammatory and autoimmune diseases, including suspected acute appendicitis of children [19], activated ulcerative colitis [12], rheumatoid arthritis [20,21], adultonset Still's disease [22] and asthma [23]. Especially, Ahn et al found serum LRG, namely LRG1, is elevated in patients with SLE and correlates with disease activity [24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, LRG1 is identified as an inflammatory protein in human serum and highly expressed in various kinds of benign inflammatory and autoimmune diseases, including suspected acute appendicitis of children [19], activated ulcerative colitis [12], rheumatoid arthritis [20,21], adultonset Still's disease [22] and asthma [23]. Especially, Ahn et al found serum LRG, namely LRG1, is elevated in patients with SLE and correlates with disease activity [24].…”
Section: Introductionmentioning
confidence: 99%
“…In active LN, the inflammatory and autoimmune reactions were more serious. In previous study, serum LRG1 concentrations correlated with disease activity in rheumatoid arthritis, Crohn's disease, ulcerative colitis and adult-onset Still's disease [12,20,22,31].…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, LRG1 is identified as an inflammatory protein in human serum and highly expressed in various kinds of benign inflammatory and autoimmune diseases, including suspected acute appendicitis of children [19], activated ulcerative colitis [12], rheumatoid arthritis [20,21], adultonset Still's disease [22] and asthma [23].…”
Section: Introductionmentioning
confidence: 99%